2020
DOI: 10.1186/s40001-020-00408-3
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of miR-19b-3p in patients with sepsis and its regulatory role in the LPS-induced inflammatory response

Abstract: Background: MicroRNAs (miRNAs) play important roles in the development and progression of sepsis. This study investigated the clinical value of miR-19b-3p in sepsis patients, and explored its role in regulating inflammatory responses in HUVECs cells. Methods: 103 patients with sepsis and 98 healthy individuals were recruited. qRT-PCR was used for the measurement of miR-19b-3p level. Cell viability was evaluated using CCK-8. The protein levels of TNF-α and IL-6 were measured using ELISA. Receiver operating char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…34 In addition, protective roles of miR-19b-3p in patients with sepsis have been identified as well by relieving the levels of pro-inflammatory factors IL-6 and TNF-α. 35 MiR-19b-3p was also reported to attenuate IL-1β-induced inflammatory injury in chondrocytes through targeting GRK6. 16 As for miR-1281, it has been identified as a tumour suppressor in many malignancies such as glioma, 17 osteosarcoma 36 and gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…34 In addition, protective roles of miR-19b-3p in patients with sepsis have been identified as well by relieving the levels of pro-inflammatory factors IL-6 and TNF-α. 35 MiR-19b-3p was also reported to attenuate IL-1β-induced inflammatory injury in chondrocytes through targeting GRK6. 16 As for miR-1281, it has been identified as a tumour suppressor in many malignancies such as glioma, 17 osteosarcoma 36 and gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…After removing 1978 duplicates, animal or in vitro studies, irrelevant articles, and excluded article format, a total of 83 full-text references were screened for eligibility. Finally, 22 records were included in our systematic review [ 6 9 , 14 – 31 ]. The detailed flow diagram of the study selection process is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Risk of bias is mainly derived from the index test. The conduct or interpretation of the index test introduced high risk in 6 records [ 7 , 8 , 17 , 19 , 23 , 28 ] and unclear risk in 13 articles [ 6 , 14 – 16 , 18 , 20 , 21 , 25 27 , 29 31 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study has presented that miR-19b-3p level is markedly reduced in the serum from sepsis patients in relation to healthy controls. 33 Another study has presented that Figure 7 Exosome promotes wound healing in mice. (A) Wound healing state of mice treated with PBS, Exo-NC or Exo-inhibitor, respectively (two-way ANOVA, *P < 0.05 vs the PBS group; #P < 0.05 vs the Exo-NC group).…”
Section: Discussionmentioning
confidence: 99%